Estudo psicossocial das perdas dentárias na terceira idade - Piuvezam, Grasiela (2004)
The present study seeks to understand tooth loss by investigating the social representations in the daily life of elderly individuals, thus characterizing itself as a comparative and analytic research. It is known that tooth loss is a common occurrence in elderly individuals, interfering at the psychosocial and biological levels, through its functional, esthetical and social implications. The area of oral health in Brazil is lacking studies on this topic, especially with respect to the psychosocial aspects of the elderly. The Theory of Social Representations and the Central Nucleus Theory were selected for theoretical-methodological support. The Free Association of Words Test was used, whose inducing stimulus were the words tooth loss , in which each subject was asked to associate 3 words, to respond to a questionnaire related to socio-economic conditions and containing an investigation of tooth loss, access to odontological services and the need for dental treatment, and to undergo a focus group interview. The study sample consisted of 120 individuals 60 years of age or over, resident in Natal, RN, Brazil and participants of the Live Together to Live Better group of the Basic Health Unit of Felipe Camarão Residential District and Unati (Open University of the Elderly); an interview was performed with 36 subjects. Data analysis was performed by Evoc 2000, SPSS/99, Graph Pad and Alceste softwares. The results demonstrate that the central nucleus of the social representations of tooth loss for the Live Together group emerged from the difficulty in eating categories, showing a relation between physiologic necessity, desire and pleasure from eating, not to mention the pain that resulted from justifying the tooth loss. Besides the central discourses, the following peripheral elements were gathered: difficulty in adapting to the prosthesis, treatment and difficulty in speaking. All of these categories, except the last, also comprised the class themes of the group interview. For the Unati group the central nucleus emerged from the socio-economic difficulties categories, demonstrating a narrow relation between poverty, access to health and education and esthetics, confirming in the discourse of common sense, the association between tooth loss and aging. At the margin of the central discourses was collected the peripheral element difficulty in adapting to the prosthesis, found both in the Live Together and Unati groups, which expresses the resistance of the subject to this new situation and the failure of the rehabilitation treatment in the sense of reviving the memory of their natural teeth. All of these categories also constitute the class themes of the of the group interview. Thus, through the study of the social representations, we can reveal a reality in the perspective of the social subjects, contemplating the multiple facets of the social-cultural reality experienced by these individuals